South Korean Cities as Norm-Bearing Actors in Migrant Protection: A Paradiplomatic Analysis of Sub-National Cooperation with Indonesia - Fachrurreza, Ahmad Mujaddid; Khofifah, Aprilia Erinda Sinta; Nugroho, Dimas Adi (Journal of Paradiplomacy and City Networks, 2026)
Despite the growing body of literature on paradiplomacy, its normative dimensions, particularly the role of cities in shaping migrant protection norms, remain underexplored. This article examines how South Korean cities with significant Indonesian migrant populations, specifically Ansan, Busan, and Incheon, function as norm-bearing actors within global migration governance. It explores how sub-national cooperation with Indonesian local governments facilitates the localization and institutionalization of migrant protection norms beyond conventional state-centric frameworks. Grounded in constructivist international relations theory, the study integrates Finnemore and Sikkink’s (1998) norm life cycle model with Acharya’s (2004) norm localization framework to analyze how global human rights-based migration norms are interpreted, adapted, and embedded in local governance practices. Employing a qualitative case study approach, the research draws on policy documents, municipal government reports, migrant support center publications, and secondary institutional sources from both Indonesia and South Korea. The findings identify three interrelated dimensions of city-level norm enactment. First, cities frame migrants as rights-bearing residents rather than temporary laborers. Second, they establish localized support infrastructures, including multilingual counseling services, migrant healthcare programs, and community-based welfare initiatives. Third, they participate in transnational policy learning and inter-city cooperation to strengthen migrant protection. These practices demonstrate how cities exercise norm-bearing agency by translating international migration norms into practical local governance despite their limited formal authority. Nevertheless, their capacity to influence migration governance remains constrained by South Korea’s centralized migration regime, particularly in matters of labor recruitment, visa regulation, and bilateral migration agreements. The article argues that South Korean cities constitute a distinct layer of sub-national normative governance that complements, mediates, and, in selected policy domains, extends national migration frameworks. By repositioning city diplomacy as a mechanism of normative governance rather than merely economic or cultural cooperation, this study contributes to paradiplomacy literature while highlighting the growing importance of sub-national actors in advancing rights-based approaches to migrant protection within multi-level migration governance.